2016
DOI: 10.1111/trf.13671
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for transfusion in cesarean section deliveries at a tertiary hospital

Abstract: Placenta previa was a risk factor associated with moderate transfusion, and pernicious placenta previa was the only modifiable prepartum risk factor independently associated with all transfused subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 35 publications
(60 reference statements)
2
21
0
Order By: Relevance
“…According to different literature reports, the blood transfusion rate for obstetric patients varies in developing countries (up to 25%) versus developed countries (1.1%–7.8%); however, the blood transfusion rate was 0.53% in Shanghai, which is lower than the figures reported in other studies . In our survey, the blood transfusion rate for postpartum women in 2015 was 2.94%, which is similar to that reported in developed countries.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…According to different literature reports, the blood transfusion rate for obstetric patients varies in developing countries (up to 25%) versus developed countries (1.1%–7.8%); however, the blood transfusion rate was 0.53% in Shanghai, which is lower than the figures reported in other studies . In our survey, the blood transfusion rate for postpartum women in 2015 was 2.94%, which is similar to that reported in developed countries.…”
Section: Discussionsupporting
confidence: 71%
“…Significant predictors of perinatal transfusion were identified by entering candidate risk factors (polyembryony [yes/no], anemia [yes/no], thrombocytopenia [yes/no], preeclampsia [yes/no], placenta previa [yes/no], placental implantation [yes/no], scarred uterus [yes/no], placental abruption [yes/no], residual placenta [yes/no], stillbirth [yes/no], HELLP [yes/no], hemophilia [yes/no], and heart disease [yes/no]) into a stepwise model. These risk factors have been associated with PPH or perinatal transfusion in other studies . We first conducted a series of univariate analyses for each risk factor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Placenta previa was the most common risk factor for transfusion in this study; patients with a placenta previa had a 68.8% likelihood of requiring blood transfusion. Placenta previa is a well‐known risk factor for PPH, and many studies have shown that it is the most significant risk factor for transfusion and peripartum hysterectomy . The high likelihood of transfusion in patients with a placenta previa should prompt providers to counsel patients with placenta previa and two or more prior CDs that there is a high likelihood of transfusion and to plan for this eventuality.…”
Section: Discussionmentioning
confidence: 99%
“…Massive blood transfusion used to be associated with severe morbidity; however, modern facilities have significantly improved this outcome. [910] A previous analysis of the Nationwide Inpatient Sample suggested a cause-specific peripartum hysterectomy frequency of 3.6/10,000 deliveries in the United States between 1994 and 2007. [6] In our study, 24 of the 40,231 pregnancies required hysterectomy, for an estimated 5.9/10,000 cases.…”
Section: Discussionmentioning
confidence: 99%